A new and improved structure of polysilicon resistor for subquarter micrometer CMOS device applications. - Kong-Beng Thei
A new and improved structure of polysilicon resistor for subquarter micrometer CMOS device applications has been demonstrated and studied. A simple model is proposed to analyze its important parameters such as the voltage-dependent bulk sheet resistance, interface resistance, and voltage coefficient of resistance (VCR). An anomalous voltage-dependent characteristic of overall resistance is found to mainly result from the existence of interface resistance. The proposed structure of a polysilicon resistor with a larger effective width of interface region shows substantial suppression of the voltage-dependent resistance deviation caused by interface resistance. The reduction of the VCR value is also obtained for the new structure. Consequently, from experimental results, the proposed structure can be used in precise (lower VCR) polysilicon resistors.
Keywords: Si; VCR value reduction; Anomalous voltage-dependent characteristic; Interface resistance; Model; Polysilicon resistor; Subquarter micron CMOS device applications; Voltage coefficient of resistance; Voltage-dependent bulk sheet resistance